2000
DOI: 10.1093/jnci/92.12.971
|View full text |Cite
|
Sign up to set email alerts
|

Findings From 752 081 Clinical Breast Examinations Reported to a National Screening Program From 1995 Through 1998

Abstract: CBEs performed in community-based screening programs can detect breast cancers as effectively as CBEs performed in clinical trials and may modestly improve early-detection campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
94
4
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 28 publications
15
94
4
4
Order By: Relevance
“…However, the quality of CBE in a community setting is likely to be lower. 16,17 The sensitivity of CBE supplemented with mammography is also high, which contradicts some of the criticisms of mammography quality in the CNBSS. 18 However, part of the observed high detection rate at screening is explained by an estimated 24 -29% higher breast cancer incidence rate in the trial compared to the average Canadian rate.…”
Section: Discussionmentioning
confidence: 95%
“…However, the quality of CBE in a community setting is likely to be lower. 16,17 The sensitivity of CBE supplemented with mammography is also high, which contradicts some of the criticisms of mammography quality in the CNBSS. 18 However, part of the observed high detection rate at screening is explained by an estimated 24 -29% higher breast cancer incidence rate in the trial compared to the average Canadian rate.…”
Section: Discussionmentioning
confidence: 95%
“…One recent large-scale observational study showed that among women aged 50-69, CBE contributes to cancer detection, with roughly 0.8 cancers per 1000 screens detected by CBE alone (positive CBE and benign or missing mammography results). 16 However, early detection and prognostic outcomes were not evaluated. 16 Furthermore, CBE in that setting may not have optimised the use of the clinical examination to identify subtle signs of breast cancer.…”
mentioning
confidence: 99%
“…16 However, early detection and prognostic outcomes were not evaluated. 16 Furthermore, CBE in that setting may not have optimised the use of the clinical examination to identify subtle signs of breast cancer. 17 Although clear abnormal clinical ndings including discrete palpable masses, bloody or serous nipple discharge, nipple or areolar scaliness, or skin dimpling or retraction were assessed, subtler signs such as asymmetric thickening of the breast tissue or slight asymmetry of breast contour were not examined.…”
mentioning
confidence: 99%
“…In community based studies, without the implementation of standard breast exam guidelines, CBE detected about 5 % of cancers that were not visible on mammography. 8 The Canadian National …”
mentioning
confidence: 99%
“…In community based studies, without the implementation of standard breast exam guidelines, CBE detected about 5 % of cancers that were not visible on mammography. 8 The Canadian National Published online February 23, 2013 Breast Cancer Study-2 investigated the effects of mammography alone compared to careful standardized clinical breast examination plus mammography, and found that breast cancer mortality was the same in both groups after 13 years of follow-up. 9 Cancers revealed by CBE are more aggressive compared to those found on mammogram.…”
mentioning
confidence: 99%